Opsin genes: research perspectives with Neotropical cichlids (Perciformes: Cichlidae) and their relevance in floodplain studies - Thomaz Mansini Carrenho Fabrin; Luciano Seraphim Gasques; Sonia Maria Alves Pinto Prioli; Alberto José Prioli (Acta Scientiarum: Biological Sciences, 2016)
Vision not only plays an important role in the behavior and exploration capacity of new ecology niches but also influences the evolution of species exposed to the heterogeneity of light. Floodplain environments have high habitat heterogeneity and, thus, different light gradients. Cichlids are a group of vertebrates that has stirred interest in evolutionary studies due to their morphological and behavioral diversity and their widely used vision. The molecular basis of vertebrates’ vision occurs through the interaction of opsin proteins and retinal chromophores. Proteins are expressed by opsin genes where each is responsible for absorbing certain light wavelengths.  Current review analyzes the main characteristics of opsin genes family and the possibility of using them in floodplain and Neotropical cichlids studies. Opsins may have different levels of expression and molecular polymorphisms according to the dispersion of the species. They are also related to such behavior as sexual selection, nourishment and exploration of new habitats. Floodplains are natural experiments and dynamic environments that provide a wide range of habitats. In fact, the integration of studies in floodplains and the opsin genes in Neotropical cichlids seems to be a promising and still unexplored area in Neotropical regions.